Multi-walled carbon nanotubes reinforced Inconel 718 superalloy fabricated by spark plasma sintering: Microstructure and mechanical property - Z.J. Han; L.Y. Ma; Q.S. Feng; B. Meng; M. Wan (Journal of Materials Research and Technology)
To investigate the densification and strengthening mechanisms of MWCNT/Inconel 718 composites, samples with different MWCNTs content are fabricated by spark plasma sintering (SPS) at varying sintering temperatures. The densification process, the room-temperature flexural and compression properties, the mechanical properties at high temperatures, and microstructure evolution are discussed. Increasing the sintering temperature improves material densification by reducing the number of indented pores and gully defects in the heating and holding stage. The incorporation of MWCNTs, though impeding material density by affecting the bonding of powder particles, can enhance the mechanical properties of the composites through load transfer and Orowan strengthening mechanisms. The composites prepared at 1050 °C with 0.5% MWCNTs content show a high relative density of 97%, a flexural strength of 1090 MPa, a compressive strength of 1523 MPa, and a high-temperature (1200 K) compression strength of 138.5 MPa, which are all much higher than that of Inconel 718 alloy. Finally, turbine blades with complex curved areas are prepared at a temperature of 1050 °C and an MWCNTs content of 0.5%, providing a new idea for forming high-strength superalloy matrix composites that can withstand ultra-high temperatures.